Technological Learning and Technology Mastery by 10 Companies Under the Supervision of Agency for the Management of Strategic Industries (BPIS) in Indonesia Prior to the 1998 Economic Crisis - Hermawati, Wati; Aminullah, Erman (STI Policy and Management Journal, 2023)
The research examined technological learning in the developing high-tech industry within the state-owned strategic companies under supervision of the Agency for the Management of Strategic Industries (BPIS). The research has been conducted to date on high-tech development using a technological learning approach as one method of developing the nation's S&T (Science and Technology).  This work was completed through desk research using available archives on documented reports for ten strategic industries. The research results confirmed the story of Indonesian innovation policy emphasis on technology-based industrial transformation was a real, staged process with clear concepts and objectives at strategic companies. Short-term innovation traps should be avoided for not repeating innovation discontinuity, which has become the primary concern of short-sight’s actors in technology politics. The key to successful technological learning are: i. continuous without stopping, the innovation continuity should be undertaken by confronting the crisis situation has become a requirement for innovative industrialists engaged in innovative economic activities, and; ii. companies could take alternative paths in continuous technological learning to climb the technological ladder by continuously engaging in R&D and engineering capability upgrading in the global competition sphere, because a company cannot survive without building a strong foundation of technological capabilities.Keywords: high-tech development, economic crisis, technological learning, innovation discontinuity, R&D governance.